A new approach to improve water loss control using smart metering data - Loureiro, D. (2014)
Submitted by mcsantos@lnec.pt (mcsantos@lnec.pt) on 2014-09-01T11:41:59Z No. of bitstreams: 1 Abstract_WS-EM13317R1.pdf: 20582 bytes, checksum: e2e008f2ac4d6cb46b1cc6cb94d81c70 (MD5)